Organizações comunitárias e movimentos sociais : conflitos e tensões nos espaços de participação do município de Natal - Cunha, Josemi Medeiros da (2011)
This study reflects on the conflicts that exist between the different forms of participation and the political representation manifested by community organizations and social movements in the city of Natal/RN. The objective is to better understand the process of political participation of the popular classes and how the different actors have represented collective demands in the struggle for rights. To this end, we mapped the organizations, social movements and participation spaces, through a type of participant research, in which we had the opportunity to experience and study different forms of collective action and events instigated by the community organizations and the Movement for the Struggle in the Neighborhoods, Villages and Slums (Movimento de Luta nos Bairros, Vilas e Favelas) MLB. From the theoretical contributions of authors such as Maria da Glória Gohn, Marco Aurélio Nogueira, Virginia Fontes, Vera da Silva Telles, Roberto Da Matta and Carlos Montaño, as well as the empirical data collected, the study revealed that on representing their segments and occupying different spaces of participation, some actors have formed partnerships with the State, putting collective demands on a second plane. Contrarily, other actors have articulated their struggle around collective demands and manifested through direct action, mobilizing and asserting themselves in defense of a project for society